Analysis of Financial and Digital Literacy Aspects in Modern Economy: Combating Internet Disinformation and Hybrid Threats in OECD - Koraus, Antonin; Lukac, Jozef; Mihalcova, Bohuslava; Javorcik, Patrik; Kudlova, Zuzana (Journal of Ecohumanism, 2024)
In the current political and economic context, the world is actively addressing the issue of combating disinformation and influencing public opinion. Within the OECD, various initiatives and projects focus on strengthening citizens' critical thinking, promoting media literacy and increasing information transparency. The organization also addresses digital influence and disinformation, considering ways to enhance society's resilience to these issues. Research examines the ability of individuals to combat internet traps, hoaxes, and disinformation in OECD countries, analyzing how individuals identify and detect disinformation and false information online. The research employs various statistical methods, primarily clustering analysis, as well as the analysis of statistical relationships between variables and country comparison analysis. The research indicators are based on OECD data from 2022. The study's results provide useful information for cyber security experts, policymakers, and the general public who are working to combat the spread of disinformation, hybrid threats and hoaxes on the internet.